Characterisation Of Lactic Acid Bacteria And Bifidobacteria And Their Potential Application As A Probiotic Against Infant Diarrhea - Haque, K.M.formuzul (2000)
The major health promoting probiotic bacteria found in the human gut are of the genera Bifidobacterium and Lactobacillus. The main objectives of the present studies were to isolate, characterise and identify the suitable probiotic strains of Lactobacillus (LAB) and Bifidobacteria (BB) from faeces of breast fed infants which could be used as effective probiotic for the control of infant diarrheal diseases. From the isolation studies, the Lactobacillus was found to be Gram-positive, non-motile, short rods and catalase, nitrate, oxidase negative. The Bifidobacteria were Gram-negative, curved with characteristics of Y and V shapes. The high performance of liquid chromatography (HPLC) showed that almost all strains of BB produced more or less or equal amount of acetic and lactic acids. Based on the carbohydrate fermentation profile using API-CH-50 kits, out of 21 Lactobacillus, 16 species belong to the L. casei, four to L . brevis, one species to L. plantarum and one sub species casei. Twenty of Bifidobacteria were B. infantis species, where 13 belong to subspecies infantis, 7 were lacentis The antagonistic activities of LAB and BB were tested against ETEC E.coli 01 57:H7 and Salmonella typhimurium S-285 using double layered assay, results showed that strains LAB-3, 11, 21 and Bifi- l l , 1 9, 20 produced wider inhibition zone compared to others.